La gestión del cambio de las empresas familiares: sus riesgos y retos en Bogotá - Colombia (2021)
This document constitutes a scientific research article, product of the doctoral thesis project for the International Iberoamerican University, on which the adaptability of family businesses mm Bogotá Colombia to new markets 1s evaluated and studied precisely. im direct relation to the limitations or strengths offered by the existing legislation on the matter, this with the ultimate aim of fostermg spaces for reflection and improvement strategies 1n the processes of strategic change management of To the companies studied. The model used 1s of a mixed, paradigmatic and disciplinary nature, within the method of participation action research. The o identification of these favorable or unfavorable elements for the companies m terms of change management offers a broader vision of the characteristics of family companies, lays the basis of their social and economic significance; This process also establishes the essential needs for the professionalization of human capital and favorablestrategies for the consolidation of strategic management processes andmeasurement of financial goals for small and medium-sized companies.